Development of dynamic model of body supported knee swing exercise with powered orthosis for lowered limb rehabilitation - Raisha, Awanis (2017)
This paper presents the development of body supported knee swing exercise with powered orthosis for lower limb rehabilitation. Knee swing with powered orthosis is subjects in helping stroke patients with gait disorder. This gait disorder is referring to hemiplegia patient. Hemiplegia can be defined as that complete paralysis of half of the body, this term is also similar to hemiparesis which is weakness on one side of the body. This lower limb rehabilitation is modeled in MSC.VisualNastran 4D 2003, and all the knee joint movement are controlled in Matlab/Simulink simulation. The control system was conducted by using PID controller in determining the knee position and the knee angle of a hemiplegia patient for this rehabilitation purpose. The tests were carried out at different gain and without controller at all. Results presented with controller gives more accuracy compared to the system without controller. Stroke rehabilitation is an important part of recovery after stroke and the goal of this program is to help relearn skills that are lost when stroke affected part of the body. Proportional Integral Derivative (PID) controller is used as the controller to control the left side lower limb of humanoid that attached to the knee orthosis by using Matlab/Simulink exportation. By using PID controller, the knee angle movement is becoming smooth as the average trajectory error was reducing compared to the P controller. The comparison of the performance of the stimulated exercise without controller and with PID was evaluated. From the result, a good knee flexion and extension movement was obtain during PID compared to the without controller. This can be approved when the knee flexion will follow the predefined knee trajectory.